Computed Tomography in Differential Diagnosis of Exudative and Transudative Pleural Effusions - Thiravit, Phakphoom; Juengsomrasong, Piyanus; Thiravit, Shanigarn (Siriraj Medical Journal, 2017)
Objective: To differentiate between exudative and transudative pleural effusions by using CT attenuation values and CT appearances. Methods: The retrospective study reviewed 132 patients who were diagnosed of pleural effusions in 2007-2014. All patients were evaluated by chest CT images before or after pleural tapping within 2 days. Pleural effusions were classified as exudates or transudates based on Light’s criteria.1 Pre-contrast and post-contrast CT images were reviewed by measuring the mean attenuation values of pleural effusions and the associated CT findings. Results: Pleural effusions were 112 exudates and 20 transudates. Exudate group had significant higher mean attenuation values, compared with a transudate, in both pre-contrast (12.8±5.0 HU vs. 9.4±5.2 HU; p<0.001) and post-contrast images (13.8±5.1 HU vs. 10.2±5.7 HU; p=0.006). For differentiation between types of pleural effusions, the CT attenuation cutoff value of 8.5 HU showed highest sensitivity of 84.5% and the cutoff value of 16 HU showed highest specificity of 95%, respectively. The CT findings of pleural nodule, pleural thickening and loculation were more common in exudates, compared with transudates with the statistical significance and specificity of those findings as high as 100%, 90%, and 75%, respectively. Conclusion: The mean attenuation values of ≥16 HU favor exudates. However, the use of CT attenuation values for differentiating types of pleural effusions alone, showed poor diagnostic performance. Correlation with clinical context and pleural fluid analysis are still essential. We suggest the three helpful CT findings for diagnosis of exudates which are pleural thickening, pleural nodules and loculation.